Review of Osteoporotic Fractures: Occurrence, Prevention, and Consequences - Elias, Nelson; Ribeiro, José Eduardo Grandi; Campinho, Luiz Augusto; Reis, Cilas; Elias, Luiz Arthur Miguelote S.; Labronici, Pedro José (Revista Brasileira de Ortopedia, 2025)
Osteoporosis is a metabolic condition that compromises bone density and architecture, increasing the risk of fractures and impacting morbidity and mortality. The diagnosis involves bone densitometry, in which mineral density in areas prone to fractures is assessed. Primary osteoporosis is age-related and may remain asymptomatic for years, while secondary osteoporosis results from comorbidities or medications. Approximately 80% of postmenopausal Caucasian women have osteoporosis, with an expected increase with aging. Orthopedic treatments are common for fractures, which are often caused by falls in the elderly. Fracture prevention requires public health policies and therapies focused on this goal.
Keywords: diagnosis; fractures, stress; osteoporosis; risk assessment; treatment